Exploring the geometrical structures of X©BnHnm [(X, m) = (B, +1), (C, +2) for n = 5; (X, m) = (Be, 0), (B, +1) for n = 6] by an electronic method. (7th September 2015) - Hou, Jianhua; Chen, Ying; Duan, Qian; Liang, Qingcheng; Jiang, Dayong; Liu, Wanqiang; Yan, Bing; Li, Zhiru; Gu, Fenglong; Li, Qianshu
Abstract : The (quasi-)planar wheel-type structures can be obtained by adding electrons. Abstract : A series of singlet and triplet wheel-type clusters obtained through an electronic method, i.e., adding two and four electrons into X©B n H n m [(X, m ) = (B, +1), (C, +2) for n = 5; (X, m ) = (Be, 0), (B, +1) for n = 6], have been studied theoretically. With the increase of the number of electrons, the sizes of peripheral boron rings tend to decrease due to the increase of negative charges on the boron rings. The results of the kinetic stability and the electronic stability suggest that the triplet C©B5 H5 and singlet Be©B6 H6 are stable and may be detected experimentally. Nucleus-independent chemical shift and molecular orbital analysis reveal that some wheel-type clusters with the planar ring possess aromaticity properties that are attributed to the delocalized π electrons conforming to the Huckel rule, i.e. 4 n + 2 for singlets or 4 n for triplets. These findings from this work are significant for designing novel wheel-type clusters.